As if by Magic: An Abrupt Change in Motion Direction Induces Change Blindness. (March 2019) - Yao, Richard; Wood, Katherine; Simons, Daniel J.
Magicians claim that an abrupt change in the direction of movement can attract attention, allowing them to hide their method for a trick in plain sight. In three experiments involving 43 total subjects, we tested this claim by examining whether a sudden directional change can induce change blindness. Subjects were asked to detect an instantaneous orientation change of a single item in an array of Gabor patches; this change occurred as the entire array moved across the display. Subjects consistently spotted the change if it occurred while the array moved along a straight path but missed it when it occurred as the array changed direction. This method of inducing change blindness leaves the object in full view during the change; requires no additional distractions, visual occlusion, or global transients; and worked in every subject tested here. This phenomenon joins a body of magic-inspired work that yields insights into perception and attention.